Immunodeficiency in DiGeorge Syndrome and Options for Treating Cases with Complete Athymia - Davies, E G. (Frontiers in Immunology, 2013)
The commonest association of thymic stromal deficiency resulting in T cell immunodeficiency is the DiGeorge syndrome (DGS). This results from abnormal development of the third and fourth pharyngeal arches and is most commonly associated with a microdeletion at chromosome 22q11 though other genetic and non-genetic causes have been described. The immunological competence of affected individuals is highly variable, ranging from normal to a severe combined immunodeficiency when there is complete athymia. In the most severe group, correction of the immunodeficiency can be achieved using thymus allografting which can enable thymopoeisis in the absence of donor-recipient matching at the major histocompatibility loci. This review focusses on the causes of DGS, the immunological features of the disorder and the approaches to correction of the immunodeficiency including the use of thymus transplantation.